1981
DOI: 10.1021/j150603a009
|View full text |Cite
|
Sign up to set email alerts
|

Studies on spin-trapped radicals in .gamma.-irradiated aqueous solutions of L-proline and trans-4-hydroxy-L-proline by high-performance liquid chromatography and ESR spectroscopy

Abstract: The short-lived radicals generated in 7-irradiated aqueous solutions of either L-proline (I) or trans-4hydroxy-L-proline (II) were investigated by spin trapping with 2-methyl-2-nitrosopropane and subsequently by high-performance liquid chromatography combined with ESR spectroscopy. Four ESR spectra of the spin adducts could be obtained from I and two from II, which were separated individually. The stability differences between these spin adducts are discussed in relation to the structures of the adducts.Co. Lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Conclusions from the present and previous works (14)(15)(16)(17)(18)(19)(20)(21)(22) will b e utilized for a general discussion o n radiolysis of proteins in aqueous solutions, with conclusions o n amino acids and peptides with functional o r aromatic groups in side-chains, which will b e presented in the future.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Conclusions from the present and previous works (14)(15)(16)(17)(18)(19)(20)(21)(22) will b e utilized for a general discussion o n radiolysis of proteins in aqueous solutions, with conclusions o n amino acids and peptides with functional o r aromatic groups in side-chains, which will b e presented in the future.…”
Section: Discussionmentioning
confidence: 95%
“…To better analyze such spectra, high-performance liquid chromatography (hplc) has been combined with spin trapping (the spin-trap hplc-esr method), and been applied to studies on y-irradiated aqueous systems of several amino acids (14)(15)(16)(17)(18)(19)(20). The main general mechanisms found for aliphatic amino acids were reductive deamination reactions induced by e, addition to carboxyl carbons (eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have demonstrated the reactivity of EEs with amino acids and N-acetyl amino acids in neutral aqueous 11 and alkaline glasses, 12 and shown that the injected EEs induce a number of fragmentation reactions in these aqueous systems to form various radical species. In particular, it was experimentally reported that after attachment, EEs are found to add to the peptide bond or to the carboxyl group, [13][14][15] which is distinctly different from the EE-binding modes in the gas phase. [7][8][9][10] Furthermore, upon annealing, all the electron adducts undergo fragmentation of the peptide bond between the N and C a of the peptide structure, 13 or a reductive deamination reaction.…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9][10] Furthermore, upon annealing, all the electron adducts undergo fragmentation of the peptide bond between the N and C a of the peptide structure, 13 or a reductive deamination reaction. 14,15 However, the mechanism of EE interaction with amino acids and peptides in solution, especially a description of the states and dynamics of localization towards the target species of the EEs, is still lacking.…”
Section: Introductionmentioning
confidence: 99%